Interaction : a way to understand power relationships in an EFL classroom (2020)
Eng: This study emerged from the necessity of understanding the way in which power and power relationships took place within the interaction a group of students studying English. Therefore, interaction in this study was the means to analyze and understand the way in which the power relationships operated inside the English classroom. Stemming from a qualitative approach that according to Dörnyei , “…has as a main objective to describe social phenomena as they occur naturally”(2007, p.336 ). In that order of ideas, it is possible to make sure that this study does not aim to measure elements inside the classroom but rather analyze the process of interactions and relationships between a group of pre-service teachers in an English classroom and the students. As part of the analysis in the study, it is evident that there are more elements that appear or happen amidst the development of the teaching-learning process, elements such as paralinguistics and kinesthetic aspects. The fact is, beyond having knowledge of a subject matter, teachers and individuals belonging to a classroom have to be aware that the interactive process can provide important elements, as mentioned above, that account for the power dynamic inside the classroom. Similarly, this study also claims that the set of data that was gathered and analyzed in the development of this project can be used as a guide or as a referent in other studies or contexts due to the way in which power relationships are present in all contexts and human relationships where interaction takes place. So, in spite of this issue was found in a specific environment, it was possible for the researchers to perceive this issue in another environment, opening the possibility for further research ideas about this issue and its variables.